Indonesian Shariah Hospital Implementation Helping The Halal Industry’s Ecosystem: The Swot Analysis - Minarni; Wibisono, Nurharibnu; Retno Widiyanti, Dwi; Ayuningtyas, Rosida Dwi (AL-FALAH : Journal of Islamic Economics, 2025)
Purpose: The purpose of this study is to analyze the strengths, weaknesses, opportunities, and threats of implementing sharia hospitals in Indonesia to help the halal industry ecosystem in Indonesia. Design/Method/Approach: This type of research is qualitative, using descriptive methods and SWOT analysis. Secondary data comes from DSN MUI Fatwa Number 107/DSN-MUI/X/2016 on Sharia-based hospital organization. Secondary data also includes Sharia hospital journals, proceedings, reports, news, and websites. Documentation is used to collect data. Data is evaluated and interpreted, and conclusions are drawn using applicable references. Findings: This study found that the implementation of sharia hospitals in Indonesia is supported by the strength of DSN-MUI Fatwa No. 107/DSN-MUI/X/2016, the enthusiasm for halal lifestyle, and the development of the MUI halal-certified medicine, food, and beverage sectors. Opportunities in the form of high market demand due to the large Muslim population and support from the tourism sector. Weakness factors include the lack of qualified human resources for Islamic hospitals and the pharmaceutical industry, which still imports raw materials that do not meet halal standards. The threat is the conventional-based Indonesian public health insurance (BPJS), which contains usury elements that do not meet Sharia principles in Islamic hospitals. Originality/Values: This research contributes to increasing awareness of the importance of sharia hospitals in Indonesia and helps formulate appropriate sharia hospital development strategies for the sustainability of the halal industry ecosystem based on the SWOT analysis results. Keywords: Health Services, Sharia Hospital, SWOT Analysis, Halal Ecosystem.